Male migrants' non-spousal sexual partnerships in the place of origin: an in-depth investigation in two rural settings of India - Ganju, Deepika (Taylor & Francis, 2013)
Male migrants in India are at disproportionately high risk for HIV, not only because of their sexual behaviours in destination areas but also due to their risk behaviours in their place of origin. While studies have documented male migrants’ risky behaviours in the home setting, few have attempted to understand the underlying socio-cultural context in which they engage in such behaviours. This paper examines the patterns and context of male migrants’ non-spousal sexual partnerships in two high-out-migration districts of India. Data, drawn from a cross-sectional behavioural mixed-methods study conducted in 2008, included a structured survey with 1272 migrants, followed by in-depth interviews with 33 male migrants. Results suggest that sexual activity was common in the place of origin: around 50% of migrants had sex with a non-spousal female partner and two-fifths had initiated sex in this setting. Migrants’ non-spousal sexual behaviours in the home village were influenced by the prevailing socio-cultural context, including migrants’ enhanced socio-economic status, attitudes to non-spousal sex and accessibility of sexual partners. Male migrants’ non-spousal sexual partnerships in source areas are influenced by socio-cultural factors, which must be considered when designing HIV programmes in India and elsewhere.